2021
DOI: 10.1016/j.celrep.2021.110145
|View full text |Cite
|
Sign up to set email alerts
|

Brain connectivity inversely scales with developmental temperature in Drosophila

Abstract: Highlights d Developmental temperature affects synapse numbers and partner availability in flies d Development at 18 C results in synaptic partnerships absent at 25 C d The same non-canonical synapses form at 18 C and in the absence of a main partner at 25 C d Adult behavioral activity is adapted for the temperature at which the fly developed

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 83 publications
2
33
2
Order By: Relevance
“…In contrast, loss of EGFR activity resulted in a significant decrease of BrpD3-GFP puncta – which colocalize with endogenous Brp (Fig.S3E,E’-F,F’) – in terminal branches from 0.22 puncta per µm to 0.1per µm. This corresponds to a 2.5-fold decrease in the total number of BrpD3 puncta from ∼15 per axon to ∼6.5 per axon and was accompanied by a redistribution from numerous small puncta at presynaptic sites into a few large BrpD3 aggregates (arrow) (Fig.3C,C’-D,D’,F,G), an indicator of loss of endogenous active zones in DCNs (Kiral et al ., 2021).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In contrast, loss of EGFR activity resulted in a significant decrease of BrpD3-GFP puncta – which colocalize with endogenous Brp (Fig.S3E,E’-F,F’) – in terminal branches from 0.22 puncta per µm to 0.1per µm. This corresponds to a 2.5-fold decrease in the total number of BrpD3 puncta from ∼15 per axon to ∼6.5 per axon and was accompanied by a redistribution from numerous small puncta at presynaptic sites into a few large BrpD3 aggregates (arrow) (Fig.3C,C’-D,D’,F,G), an indicator of loss of endogenous active zones in DCNs (Kiral et al ., 2021).…”
Section: Resultsmentioning
confidence: 89%
“…We have previously shown that the M-DCNs regulates behavioral responses in the multiparametric single fly visual response assay called Buridan’s paradigm (Linneweber et al ., 2020). In this assay, single flies walk freely between two identical visual cues (Fig.7A) and reduction of synapses causes increased fly activity when flies were tested at the same temperature at which they developed (Kiral et al ., 2021). Consistent with this, we find that inactivation of EGFR specifically in DCNs results in flies walking longer distances, staying active for a longer time, and increasing the number of walks between the two cues (Fig.7B-H; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations